Human Rights Encouragement Through Peaceful Resistance Initiatives in Rural Bogotá - Jesús Enrique Caldera Ynfante, Fernanda Navas-Camargo, Jaime Cubides-Cárdenas, (Opción, 2019)
Human Rights violations are efficiently detained through peaceful resistance which leads into positive outcomes. Coding, pointing out or classifying what is wrong is not enough. Environmental safeguards, land ownership, community consolidation and female empowerment when developed following principles of Community-Based Tourism (CBT), is the idea supported. Through longitudinal research, case study was made in rural Bogotá. Three CBT initiatives where reviewed. First contextualization is made, then examination on the principles of community-based tourism and the concept of resilience. At the end, a discussion of why the cases should be recognized as an example of Human Rights encouragement is provided